The Influence of Population, Education, and Minimum Wages on Female Work Force Absorption in West Java for the 2019-2023 Period - Cendani, Intan Anita; Badriyah, Nurul (Journal of Development Economic and Social Studies, 2026)
Female labor absorption is an important indicator of inclusive economic development; however, in West Java Province, a gap remains between the large number of women of working age and the level of their absorption in the labor market. This study aims to analyze the effects of the female working-age population, education as measured by average years of schooling, and the minimum wage on female labor absorption in West Java Province during the 2019–2023 period. This research employs a quantitative approach using panel data regression methods across 27 regencies and municipalities. The data used are secondary data obtained from the Central Statistics Agency and regulations on district and municipal minimum wage determination. The results indicate that the female working-age population has a positive and significant effect on female labor absorption, while education, the minimum wage, and the Covid-19 pandemic conditions do not have a significant effect. These findings suggest that the increase in the female population is a key factor driving female labor absorption. This study contributes to the literature on female employment and provides policy implications for local governments in formulating strategies for job creation and the sustainable improvement of female human resource quality.